IFN-γ induced the formation of foamy macrophages via CD40 signal to control Mycobacterium abscessus pulmonary infection - Zhang, Shaoyan; Feng, Ya; Wu, Xianwei; Chen, Jiajun; Zhang, Huiyong; Tian, Li; Lou, Hai; Wang, Liping; Su, Ben; Huang, Xing; Qiu, Lei; Wu, Dingzhong; et al. (Frontiers in Immunology, 2025)
BackgroundFoamy macrophages (FMs) have recently shown potential in restricting the intracellular growth of Mycobacterium. However, the mechanism behind the formation of FMs and their significance in the pathophysiology of Mycobacterium abscessus (M. abscessus)-induced pulmonary infections remains poorly understood.MethodsClinical blood samples, murine infected models (WT and IFN-γ-/- mice), and macrophage infected models were utilized to investigate the formation of FMs mediated by IFN-γ and its critical role in bacterial control during M. abscessus infection. Oil Red O staining and confocal microscopy were employed to assess the effect of IFN-γ on FMs formation in vivo and in vitro, coupled with specific signaling pathway inhibitors. Transcriptomics and lipidomics were performed to identify key pathways, genes, and lipid metabolites.ResultsDuring the acute infection phase, the lipid droplets (LDs) in peripheral blood mononuclear cells significantly increased, along with the upregulation of serum IFN-γ levels. Experiments with IFN-γ-/- mice infected with M. abscessus revealed that IFN-γ is essential for the formation of LDs or FMs during the infection. The addition of IFN-γ increased the formation of LDs or FMs and restricted the growth of M. abscessus in vitro and in vivo. Furthermore, we found that IFN-γ induced the formation of LDs required CD40-DGAT1 signaling, and a significant positive correlation between serum IFN-γ and sCD40 levels was observed. Lipidomics analysis revealed significant metabolic reprogramming in FMs, with triacylglycerols (TAGs) identified as the most significantly altered lipid species. Notably, TAGs containing fatty acid side chains such as linoleic acid and palmitic acid may play crucial roles in host defense during infection.ConclusionThis study established the IFN-γ-CD40-DGAT1 axis as an important role in the formation of FMs and the control of M. abscessus infection. These findings revealed a critical immune-metabolic pathway that may be leveraged for host-directed therapeutic interventions.